Choriocapillaris and retinal vascular plexus density of diabetic eyes using split-spectrum amplitude decorrelation spectral-domain optical coherence tomography angiography - Conti, Felipe F; Qin, Vivian L; Rodrigues, Eduardo B; Sharma, Sumit; Rachitskaya, Aleksandra V; Ehlers, Justis P; Singh, Rishi P (British journal of ophthalmology, 2019)
Split-spectrum amplitude decorrelation angiography for spectral-domain optical coherence tomography has enabled detailed, non-invasive assessment of vascular flow. This study evaluates choriocapillaris and retinal capillary perfusion density (CPD) in diabetic eyes using optical coherence tomography angiography (OCTA). Records of 136 eyes that underwent OCTA imaging at a single institution were reviewed. Eyes were grouped as non-diabetic controls (37 eyes), patients with diabetes mellitus (DM) without diabetic retinopathy (DM without DR, 31 eyes), non-proliferative diabetic retinopathy (NPDR, 41 eyes) and proliferative diabetic retinopathy (PDR, 27 eyes). Quantitative CPD analyses were performed on OCTA images for assessing perfusion density of the choriocapillaris and retinal plexus for all patients and compared between groups. Eyes with NPDR and PDR showed significantly decreased choriocapillaris CPD compared with controls, while DM eyes without DR did not show significant change. Choriocapillaris whole-image CPD was decreased by 8.3% in eyes with NPDR (p<0.01) and decreased by 7.1% in eyes with PDR (p<0.01). Choriocapillaris parafoveal CPD was decreased by 8.9% in eyes with NPDR (p<0.01) and decreased by 8.2% in eyes with PDR (p<0.01). Compared with controls, only eyes with PDR showed significantly decreased retinal CPD, as well as significantly increased foveal avascular zone (FAZ) area. In those patients, retinal whole-image CPD was decreased by 9.7% (p<0.01), retinal foveal CPD was decreased by 20.5% (p<0.01) and retinal parafoveal CPD was decreased by 11.4% (p<0.01). FAZ area was increased by 50.9% (p<0.01). Choriocapillaris and retinal CPD are reduced in diabetic retinopathy, while FAZ area is increased in eyes with PDR. Vascular changes captured by new imaging modalities can further characterise diabetic choroidopathy.